Different pathophysiology of impaired glucose tolerance in first-degree relatives of individuals with type 2 diabetes mellitus - Emerson, Peter; Van Haeften, Timon W.; Pimenta, Walkyria; Plummer, Elena; Woerle, Hans J.; Mitrakou, Asimina; Szoke, Ervin; Gerich, John; Meyer, Christian (Elsevier, 2009)
To assess whether an increased genetic predisposition for type 2 diabetes mellitus (T2DM) influences the contributions of insulin resistance and impaired insulin secretion to impaired glucose tolerance (IGT), 437 subjects not known to have T2DM underwent an oral glucose tolerance test and a 3-hour hyperglycemic clamp. Plasma insulin responses and insulin sensitivity were compared between all subjects (unselected for demographic or anthropometric characteristics) who had normal glucose homeostasis and no first-degree T2DM relative (n = 133), IGT with a first-degree T2DM relative (IGT/FH+, n = 74), or IGT without a first-degree T2DM relative (IGT/FH-, n = 50). Compared with those with normal glucose homeostasis, first- and second-phase plasma insulin responses were reduced approximately 45% and 30%, respectively (both P < .001), in IGT/FH+, whereas insulin sensitivity was only approximately 20% reduced (P = .011). In contrast, in IGT/FH-, first-phase plasma insulin responses were only approximately 20% reduced (P = .016), second-phase plasma insulin responses were not reduced, but insulin sensitivity was approximately 40% reduced (P < .001). The IGT/FH+ group differed significantly from the IGT/FH- group by having 25% to 30% lower first-phase plasma insulin responses (P = .026) and 25% to 30% greater insulin sensitivity (P = .027). Adjustment for obesity abolished the differences in insulin resistance but not plasma insulin responses. However, when the IGT groups were stratified into subgroups based on body mass index (BMI), first-phase plasma insulin responses were approximately 30% lower in IGT/FH+ with a BMI of at least 27 kg/m2 (P = .018) but similar in IGT/FH+ with a BMI less than 27 kg/m2 compared with the corresponding IGT/FH- subgroups. We conclude that, in IGT, an increased genetic predisposition for T2DM increases the contribution of impaired insulin secretion to its pathophysiology. This effect is enhanced by obesity.